Modification of the National Early Warning Score (NEWS) Observation Sheet for Patient Emergency Conditions in Hospitals - Siti Sulaiha; Ima Nadatien; Eppy Setiyowati (Journal Of Nursing Practice, 2024)
Background: Currently, the trend of patients admitted to the hospital is increasingly complex and has many co-morbidities, some of which the patient's condition will suddenly worsen or become critical, due to various interrelated causes such as weak monitoring systems and staff reactions to emergencies. Delays in treatment or inadequate care for patients who are treated in the Hospital Ward can result in several adverse conditions, namely increased patients transferred to the ICU (Intensive Care Unit), increased LOS (Lenght of Stay) in the hospital, heart attacks, or patient death. Purpose: The purpose of this study to analyze the differences in the modification of the NEWS observation sheet on the emergency conditions of patients at the hospital. Methods: The type of research used is quasi-experimental with a pre-test-post-test control group design. With a population of 160 patients and a total patient sample of 62 patients with 31 patients for the intervention group and 31 patients for the control group. How to take samples with purposive sampling technique. The independent variables in this study were the NEWS observation sheet and the NEWS modification, while the dependent variable was the patient's emergency condition. The instruments in this study were NEWS observation sheets and NEWS modifications, integrated patient development record sheets, pre-test and post-test sheets. Data analysis used Wilcoxon test and Mann Whitney test with a value of α = 0.05. Results: The results showed that the modification of the NEWS (National Early Warning Score) observation sheet with a graphic was more influential than the NEWS observation sheet in increasing vital sign monitoring with p=0.00, while the NEWS observation sheet as a control had an influence with a significant level of p=0.043, both the model shows that it is equally influential in detecting changes in patient conditions and as an aid in communicating with other health workers. Conclusion: The conclusion of this study is that after being given a modified NEWS observation sheet which is a scoring system that is simple, practical and proven to increase alertness and response to signs of bad physiological changes so that patient safety can be monitored optimally and mortality rates can decrease.